Spremembe rabe tal v slovenskem alpskem svetu - Petek, Franci (Geografija Slovenije, 2005)
The study deals with changes in land use in the 19th and 20th centuries in Slovenia's alpine region. The aim of the research was not only to study the changes in land use but also to determine the relationship between changes in land use and relief elements and their connection with sociogeographical factors and their development.Land use is a dynamic element of the landscape that is studied with the help of various resources. Special attention was given to determining the accuracy of the sources used to enable a correct interpretation of the results. Because of the uniform and only slightly changed methodology of collecting data employed since the first established stable (Franciscan) cadastre in the first half of the 19th century, it was confirmed that the data on land use from the land register is a very suitable source, primarily for establishing changes in land use over longer periods and for larger spatial units (mezzo-regions, regions), in spite of its otherwise lagging behind the actual situation.